Evaluation of embryo collection and transfer days on pregnancy rate of Mangalarga Marchador mares during the breeding season - José C. Ferreira-Silva (Universidad de Antioquia, 2019)
Background: Proper timing for embryo collection and transfer in horses -which is critical for the success of this biotechnology- is still debated. Additionally, there is little information on this technology under tropical conditions. Objective: To determine the best day for collection and transfer of embryos in Mangalarga Marchador mares under Brazilian northeast’s conditions. Methods: Donors (n= 30) and recipients (n= 76) in diestrus phase were selected based on both clinical and gynecology examinations. Estrus was induced on both donor and recipient mares by intramuscular injection of 5 mg Dinoprost, aiming to obtain an ovulation interval of -1 to +3 between recipient and donor. Ovulation was induced with buserelin acetate when the largest follicle reached at least 35 mm in diameter. At this time, mares were subjected to artificial insemination at 48-hour intervals until ovulation. The embryos were collected on days 7, 8, and 9 after ovulation. Results: The embryo collection on day 8 was more efficient (p<0.05) than on day 7, but it was not more effective (p>0.05) than day 9, which presented the same efficiency (p>0.05) as day 7. From a total of 76 embryos transferred to the recipients, that were between days 4 and 9 after ovulation, there was no influence (p>0.05) of the day of transfer on pregnancy rate. Conclusions: The embryo collection must be performed on day 8 after ovulation, and transfer can be performed on any day of that interval (4-9) without affecting the pregnancy rate.